If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 4 = -8 Reorder the terms: 4 + 3t = -8 Solving 4 + 3t = -8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3t = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 3t = -8 + -4 3t = -8 + -4 Combine like terms: -8 + -4 = -12 3t = -12 Divide each side by '3'. t = -4 Simplifying t = -4
| -2u-3=3u+2 | | x-a-b/c | | x^6-126x^3+125=0 | | (3/16)/(11/4) | | 1/4r=18-22 | | 2x-2(2x+2)=6 | | 41-1/3b=37 | | x^8+x^7+x^6=0 | | 5*3/4-1 | | 900+900+3x=700+500+9x | | 1/2I+9=14 | | 3x-3(4x-17)=96 | | 8y/12=6/9 | | 5x-11=35 | | 3*(3/4)^2-2*3/4 | | 4(c+6)=1/2(-2c-20) | | -4x+3(3x-17)=-76 | | 4b-4-11b-6= | | c-2/2+12=36 | | 0=0.001(0.732x^2+15.417x+605.738) | | 900+900+3x=700+500+9z | | x+1=7x | | 5x+12=4x+8 | | 49-49+81= | | 5x-2(6x+12)=53 | | 6x-3(6x-10)=162 | | x+10/2=42 | | 2x-2(2x-3)=-6 | | 2(x+4)=5xw+1 | | -3+-3+-2+-2+-2+-2+-1+-1+0+0+1+1+3+4= | | 4=(2+x)/2 | | 10j-10=3j-5 |